Aplikasi Metodologi Yusuf Al-Qardhawi Dalam Interpretasi Hadis Laknat Bagi Peziarah Wanita - Insan Labib, Muhammad Alfreda Daib; Nurhaedi, Dadi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
This research discusses about interpretation of hadith which explains that women who make grave pilgrimages will be cursed by Allah or Rasulullah. In this research, the methodology used is the methodology of interpreting Hadith of Yusuf al-Qardhawi. The research methodology used is descriptive-analysis, namely carrying out a description of the data collected, then carrying out an in-depth analysis to achieve the research objectives. Among the discussions in this research are, 1). Presentation of data regarding hadith and al-Jarḥ wa al-Ta'dīl hadith transmitter that will be examined. 2). Takhrīj hadith Curse for female pilgrims in kutub al-tis’ah. 3). Interpretation of the cursed hadith for female pilgrims using Yusuf al-Qardhawi's meaning methodology. This research concludes that 1). The main hadith used is the cursed hadith for female pilgrims narrated by Abu Hurairah. This hadith has saḥīḥ qualities. The reason is, all of the hadith transmitters have al-Jarḥ wa al-Ta'dīl good status and does not affect about hadith quality. 2). There are 15 same hadiths and seven similar hadiths. Among the seven hadiths, four allow grave pilgrimage for women, and the remaining three prohibit it. 3). Based on the interpretation of the hadith through Yusuf al-Qardawi's methodology, it is mentioned that women pilgrims who will be cursed by God are women who make pilgrimages very often and excessively.